Hemoparasites in a wild primate: Infection patterns suggest interaction of Plasmodium and Babesia in a lemur species. Issue 3 (December 2015) - Springer, Andrea; Fichtel, Claudia; Calvignac-Spencer, Sébastien; Leendertz, Fabian H.; Kappeler, Peter M.
Abstract: Hemoparasites can cause serious morbidity in humans and animals and often involve wildlife reservoirs. Understanding patterns of hemoparasite infections in natural populations can therefore inform about emerging disease risks, especially in the light of climate change and human disruption of natural ecosystems. We investigated the effects of host age, sex, host group size and season on infection patterns of Plasmodium sp., Babesia sp. and filarial nematodes in a population of wild Malagasy primates, Verreaux's sifakas ( Propithecus verreauxi ), as well as the effects of these infections on hematological variables. We tested 45 blood samples from 36 individuals and identified two species of Plasmodium, one species of Babesia and two species of filarial nematodes. Plasmodium spp. and Babesia sp. infections showed opposite patterns of age-dependency, with babesiosis being prevalent among young animals, while older animals were infected with Plasmodium sp. In addition, Babesia sp. infection was a statistically significant negative predictor of Plasmodium sp. infection. These results suggest that Plasmodium and Babesia parasites may interact within the host, either through cross-immunity or via resource competition, so that Plasmodium infections can only establish after babesiosis has resolved. We found no effects of host sex, host group size and season on hemoparasite infections. Infections showed high prevalences and did not influence hematological variables. This preliminary evidence supports the impression that the hosts and parasites considered in this study appear to be well-adapted to each other, resulting in persistent infections with low pathogenic and probably low zoonotic potential. Our results illustrate the crucial role of biodiversity in host-parasite relationships, specifically how within-host pathogen diversity may regulate the abundance of parasites. Graphical abstract: Highlights: Wild primates, Verreaux's sifakas, are naturally infected with 5 hemoparasite species. Plasmodium sp. and Babesia sp. infections show opposite patterns of age-dependency. This suggests within-host parasite interaction via cross-immunity or competition. Infection status did not influence hematology values, indicating low pathogenicity.